Identification and The Prevalence of Gastrointestinal Endoparasite in Long-Tailed Macaque (Macaca Fascicularis) in Wonorejo and Gunung Anyar Mangrove Eco-Tourism Surabaya - Fauziyah , Nafisah Nurti; Lastuti , Nunuk Dyah Retno; Damayanti , Ratna; Koesdarto , Setiawan; Suprihati , Endang; Witaningrum, Adiana Mutamsari (Faculty of Veterinary Medicine Universitas Brawijaya, 2023)
This study aimed to determine the types of endoparasites and their prevalence in Macaca fascicularis in the Wonorejo and Gunung Anyar mangrove forests, Surabaya. A total of 90 samples of Macaca fascicularis faeces were collected from two different mangrove forests, 45 samples from Wonorejo and 45 from Gunung Anyar. All samples were examined using sedimentation and floating methods to identify endoparasite species. Further, the number of eggs and oocysts per gram of feces was counted using the McMaster method. Results showed that 26.67% (12/45), and 22.2% (10/45) of the faecal samples were detected positive for endoparasite at Wonorejo and Gunung Anyar mangrove forests, respectively. The prevalence of parasitosis in M. fascicularis from Wonorejo was 17.7% (8/45) for Taenia sp. and 8.8% (4/45) for Balantidium coli cyst. On the other hand, M. fascicularis from Gunung Anyar was infested by Trichuris sp. at a prevalence of 22.2% (10/45). The total number of eggs and cysts ranged from 30 – 400 per gram of faecal samples. The study provides new knowledge on the parasitic burdens among long-tailed macaques in East Java.